Treatment and Postinterventional Management of a Fusiform Intracranial Aneurysm in a Professional Soccer Player: A Case Report - Etter, Manina Maja; Bonati, Leo; Tsogkas, Ioannis; Hutter, Gregor; Blackham, Kristine; Guzman, Raphael; Psychogios, Marios-Nikos (Frontiers in Neurology, 2022)
Introduction: While intracranial aneurysms are common lesions affecting between 1 and 5 percent of the general population, the prevalence in professional athletes remains unknown. The result is uncertainty and lack of guidelines on appropriate treatment of these patients. Case presentation: A 29-year old professional soccer player presented in our hospital with an incidentally found intracranial aneurysm. After detailed depiction of the aneurysm and interdisciplinary discussion, endovascular treatment using a flowdiverter was chosen to be the best treatment modality. Postinterventional medication consisted of dual antiplatelet therapy with aspirin and clopidogrel. The main challenge in managing our patient’s case was the combination of the dual antiplatelet treatment regime with his professional career in a contact sport. Conclusion: Due to the lack of literature or similar reports regarding the management of professional athletes with intracranial aneurysms the optimal treatment strategy remains unclear. Even though decisions should be made dynamically and case-adapted to each situation, developing a registry could help to provide guidance and new ideas for similar cases in the future.